Коливальний спектр р-амілоксібензиліден-р-толуідіну в кристалічній фазі - Pogorelov, V.Ye.; Bukalo, V.P.; Zhovtobriukh, I.M. (Publishing house "Academperiodika", 2022)
The Raman spectrum of p-amyloxybenzylidene-p-toluidine (ABT) liquid crystal in the crystalline phase has been analyzed. The spectrum was recorded in a spectral range of 0–165 cm–1 and at room temperature (T = 293 K). The quantum-chemical computer simulation of a molecular geometry has been carried out, and the vibrational frequencies of ABT molecules have been calculated by applying the B3LYP/6-31G(d, p) method. The results of quantum-chemical computer simulation were used to interpret the experimental Raman spectrum. The conformational parameters of ABT molecules in the crystalline phase have been determined.